The effect of cocaine and imipramine on tyramine-induced release of noradrenaline-(3)H from the rat vas deferens in vitro - Barnett, A. (1969)
1. Tyramine 10(-4)M significantly increased release of noradrenaline-7-(3)H (NA-7-(3)H) from rat vas deferens in vitro. 2. Neither cocaine 10(-5)M nor imipramine 10(-7)M-10(-6)M significantly reduced tyramine-induced release of NA-7-(3)H. 3. Increasing the exposure time to cocaine and imipramine from 10 to 20 min or pre-incubating the tissue with a wide range of NA-7-(3)H concentrations (3·3-333·3 ng/ml.) did not affect the lack of inhibition by cocaine and imipramine. 4. It is suggested that the tyramine receptor in rat vas deferens differs from that in other systems and that blockade of tyramine-released noradrenaline at α-adrenergic receptors may be the most important mechanism for tyramine antagonism by imipramine-like drugs in this tissue.